Discrete Event Systems Specifications Modelling and Simulation of Wireless Networking Applications. Issue 1 (2nd January 2022) - Tavanpour, Misagh; Kazi, Baha Uddin; Wainer, Gabriel
ABSTRACT: We discuss the use of formal discrete-event modelling and simulation for networking applications, in particular, for mobile networks and Wireless Sensor Networks (WSN). We show how one can develop discrete-event model libraries based on the DEVS formalism for mobile networks, allowing tracking the users' upload status in a given area of coverage, while using a non-cooperative algorithm or Coordinated Multipoint (CoMP) synchronisation. We show a DEVS model library for CoMP-based networks, showing how control messaging can be managed among Evolved Node Base stations (eNBs). We build a case study comparing two CoMP approaches: Joint Processing (JP) and Coordinated Scheduling (CS). Finally, we show how DEVS models can be used to model malware propagation in wireless sensor networks based on epidemic theory.